Preparation method of lithium iron phosphate material, lithium ion battery and electric equipment

By accurately controlling the molar ratio of raw materials and high-temperature treatment process, the chemical structure and particle size distribution of lithium iron phosphate materials are optimized, the shortage of fast charging performance of lithium iron phosphate batteries is solved, the capacity and compaction density are improved, and the overall performance of the battery is improved.

CN119591075APending Publication Date: 2025-03-11ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411772566.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing lithium iron phosphate batteries have shortcomings in fast charging performance, resulting in a decrease in battery capacity and energy, affecting the endurance of the entire vehicle.

Method used

By accurately controlling the molar ratio of lithium source to iron source, iron source and phosphorus source, the stoichiometric ratio of the material is optimized and structural defects are reduced; a good crystal structure is formed in combination with high-temperature treatment process, the compaction density of the powder is improved, and the particle size distribution of the material is optimized through pulverization treatment.

Benefits of technology

The capacity and powder compaction density of lithium iron phosphate materials are improved, the fast charging performance and overall first charge and discharge efficiency of lithium-ion batteries are improved, and the cycle life is extended, while maintaining high safety and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a preparation method of a lithium iron phosphate material, a lithium ion battery and electric equipment, and relates to the technical field of batteries. The method comprises the following steps: mixing raw materials of an iron source, a lithium source and a phosphorus source with a reagent serving as a reducing agent and a carbon source, and grinding to obtain precursor powder; wherein the molar ratio of the lithium source to the iron source is 1.03-1.05, and the molar ratio of the iron source to the phosphorus source is 0.965-0.99; carrying out high-temperature treatment on the precursor powder in an inert atmosphere to obtain a lithium iron phosphate base material; and crushing the lithium iron phosphate base material to obtain the lithium iron phosphate material meeting the particle size requirement. The high-capacity and high-compaction lithium iron phosphate material is obtained by accurately controlling key indexes such as the iron-phosphorus ratio, the carbon content, the graphitization degree and the particle size and combining an optimized processing technology, so that the fast charging performance of a lithium ion battery is improved, and the effect of not reducing the electric quantity while the fast charging requirement is met is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a method for preparing a lithium iron phosphate material, a lithium ion battery and electrical equipment. Background Art

[0002] As the positive electrode material of lithium-ion batteries, lithium iron phosphate has been widely used in the field of power batteries due to its advantages such as high safety, long cycle life and relatively low cost. However, with the growing market demand for fast charging, batteries face new challenges in fast charging performance. In order to improve the fast charging performance of batteries, it is usually necessary to reduce the surface density compaction, and the reduction in surface density will lead to a reduction in battery capacity and energy, thereby affecting the endurance of the vehicle. Therefore, in order to meet the demand for fast charging without reducing the power, it is extremely important to increase the capacity and powder compaction density of lithium iron phosphate, the positive electrode material. Summary of the invention

[0003] The present application provides a preparation method of lithium iron phosphate material, a lithium-ion battery and electrical equipment, which are used to improve the capacity and powder compaction density of lithium iron phosphate, a positive electrode material, so as to meet the fast charging demand without reducing the power.

[0004] In a first aspect, the present application provides a method for preparing a lithium iron phosphate material, comprising:

[0005] (1) mixing raw materials of an iron source, a lithium source, and a phosphorus source, and a reagent serving as a reducing agent and a carbon source, and grinding the mixture to obtain a precursor powder; wherein the molar ratio of the lithium source to the iron source is 1.03-1.05, and the molar ratio of the iron source to the phosphorus source is 0.965-0.99;

[0006] (2) treating the precursor powder at high temperature under an inert atmosphere to obtain a lithium iron phosphate substrate;

[0007] (3) The lithium iron phosphate substrate is crushed to obtain a lithium iron phosphate material that meets the particle size requirements.

[0008] In an optional embodiment, the mass ratio of iron to phosphorus in the lithium iron phosphate material is 1.74-1.80, the mass ratio of carbon content is 0.9-1.2%, and the degree of graphitization is 0.7-0.95.

[0009] In an optional embodiment, the lithium iron phosphate material satisfies at least one of the following: the D50 particle size of the lithium iron phosphate material is 0.9-1.5 μm; (D90-D10) / D50 of the lithium iron phosphate material is greater than or equal to 3.1; and the average primary particle size of the lithium iron phosphate material is 200-400 μm.

[0010] In an optional embodiment, in step (1), the amount of carbon source added is determined according to 0.9-1.2% of the mass of the lithium iron phosphate material.

[0011] In an optional embodiment, in step (2), the temperature of the high temperature treatment is 750-850°C.

[0012] In an optional embodiment, in step (2), the heating rate of the high temperature treatment is 5°C / min, and after reaching 750°C, the temperature is kept at 750°C for 8-16 hours.

[0013] In an optional embodiment, the iron source is selected from one or more of FeSO4, FePO4, FeCl3, FeC2O4, Fe2O3; and / or the lithium source is selected from one or more of Li2CO3, LiH2PO4, Li3PO4; and / or the phosphorus source is selected from one or more of NH4H2PO4, H3PO4.

[0014] In an optional embodiment, the reagent serving as a reducing agent and a carbon source is selected from one or more of C2H2, CH4, glucose, polyethylene glycol, sucrose, starch, H2, and CO.

[0015] In a second aspect, the present application provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer disposed on at least one side of the positive electrode collector, wherein the positive electrode active material layer is selected from the lithium iron phosphate material obtained by the preparation method described in any one of the first aspects.

[0016] On the third side, the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the positive electrode sheet as described in the second aspect.

[0017] Including the positive electrode sheet described in the second aspect.

[0018] Fourthly, the present application provides an electrical device, comprising the lithium-ion battery described in the third aspect.

[0019] The implementation of this application has at least the following beneficial effects:

[0020] 1) By precisely controlling the molar ratio of lithium source to iron source and iron source to phosphorus source, the stoichiometric ratio of the material is optimized, which helps to reduce structural defects, thereby increasing the capacity of lithium iron phosphate material and bringing it closer to the theoretical capacity;

[0021] 2) By combining the high-temperature treatment process, a lithium iron phosphate substrate with a good crystal structure is formed, the compaction density of the powder is improved, and the material that meets the particle size requirements is obtained through pulverization, which further optimizes the specific surface area and particle distribution of the material, enhances the conductivity and ion mobility of the material, and thus improves the fast charging performance of lithium-ion batteries, and improves the overall first charge and discharge efficiency and cycle life of lithium-ion batteries;

[0022] 3) Despite the improved performance, lithium iron phosphate material still maintains its high safety and cost-effectiveness, meeting the needs of fast charging without reducing power, making it continue to be competitive in the field of power batteries and able to effectively respond to technical challenges under fast charging conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0024] Figure 1 This is a SEM image of the lithium iron phosphate material provided in this application.

[0025] Description of reference numerals:

[0026] 1- Particles of lithium iron phosphate material.

[0027] The above drawings have shown clear embodiments of the present application, which will be described in more detail later. These drawings and text descriptions are not intended to limit the scope of the present application in any way, but to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] At present, the theoretical specific capacity of lithium iron phosphate positive electrode materials is 170mAh / g, but the actual charging capacity is generally 158-161mAh / g, and the discharge capacity is 155-160mAh / g. The charging capacity still has room for improvement. In addition, the first charge and discharge efficiency of lithium iron phosphate batteries is generally 89-91%, which is mainly limited by the first efficiency of the negative electrode material. Therefore, by increasing the charging capacity of the positive electrode material, the overall first efficiency and discharge capacity of the battery can be improved. In terms of material compaction, the current mass-shipped powder compaction density of lithium iron phosphate materials is 2.4-2.6g / cm³. Although the powder compaction density can be further improved by reducing the carbon content and adjusting the particle size, this usually leads to a decrease in the power performance of the material, affecting its application in fast charging cells.

[0030] In the related technologies, some high-density, high-capacity lithium iron phosphate materials based on high specific surface area iron phosphate have achieved a powder compaction density of more than 2.50g / cm³, but still do not meet the use requirements of a powder compaction density of more than 2.6g / cm³.

[0031] Based on the technical problems existing in the related technology, the embodiment of the present application takes into account the capacity, compaction and power performance of the lithium iron phosphate material by adjusting the raw material formula and combining the production process parameter control, thereby improving the capacity of the lithium iron phosphate material and the powder compaction density while ensuring the power performance, meeting the fast charging requirements without reducing the power effect.

[0032] The present invention provides a method for preparing a lithium iron phosphate material, the method comprising the following steps:

[0033] (1) Mixing raw materials of an iron source, a lithium source, and a phosphorus source and a reagent as a reducing agent and a carbon source, and grinding to obtain a precursor powder; wherein the molar ratio of the lithium source to the iron source is 1.03-1.05, and the molar ratio of the iron source to the phosphorus source is 0.965-0.99; illustratively, the molar ratio of the lithium source to the iron source can be 1.03, 1.032, 1.034, 1.036, 1.038, 1.04, 1.042, 1.044, 1.046, 1.048, 1.05 or a range consisting of any two of them, and the molar ratio of the iron source to the phosphorus source can be 0.965, 0.967, 0.969, 0.971, 0.973, 0.975, 0.977, 0.979, 0.981, 0.983, 0.985, 0.987, 0.989, 0.99 or a range consisting of any two of them. Through precise stoichiometric ratios, the ratio of lithium, iron and phosphorus in the preparation process of lithium iron phosphate material is close to the ideal stoichiometric ratio, which helps to reduce structural defects and thus improve the electrochemical properties of the material. In addition, during the synthesis process, the use of a reducing agent and a carbon source (such as glucose or sucrose, etc.) helps to provide a reducing environment at high temperature, prevents the oxidation of iron, and forms a carbon coating layer on the surface of the material. The carbon coating not only improves the conductivity of the material, but also enhances the structural stability of the material and improves the cycle performance of the lithium-ion battery.

[0034] (2) The precursor powder is treated at high temperature in an inert atmosphere to obtain a lithium iron phosphate substrate. By performing high temperature treatment in an inert atmosphere (such as argon or nitrogen, etc.), the material can be prevented from reacting with oxygen at high temperature to avoid the formation of unwanted oxides. The high temperature treatment also promotes the crystal reorganization and phase change of the precursor powder to form a lithium iron phosphate substrate with a good crystal structure, which is crucial for improving the electrochemical properties of the material.

[0035] (3) The lithium iron phosphate substrate is crushed to obtain a lithium iron phosphate material that meets the particle size requirements; considering that the particle size has a significant effect on the specific surface area, conductivity and ion mobility of the material, the lithium iron phosphate material that meets the particle size requirements is obtained by crushing, which can optimize the particle distribution and specific surface area of ​​the material, enhance the fast charging performance and overall electrochemical efficiency of the lithium-ion battery, and the appropriate particle size distribution helps to improve the compaction density of the material and the mechanical stability of the electrode.

[0036] In a specific embodiment, the particle size distribution parameters of the lithium iron phosphate material are obtained by a laser particle size analyzer. For example, the particle size distribution parameters of the lithium iron phosphate material include D50 particle size, particle size distribution width (D90-D10) / D50 and average primary particle size. Among them, D50 represents the median of the particle size, that is, 50% of the particles are less than or equal to this size; (D90-D10) / D50 represents the width of the particle size distribution, D90 and D10 represent the size that 90% and 10% of the particles are less than or equal to, respectively. By calculating (D90-D10) / D50, the uniformity of the particle size distribution can be evaluated; the average primary particle size refers to the initial particle size of the lithium iron phosphate substrate before the pulverization process. The larger average primary particle size provides sufficient mechanical strength and stability, so that a uniform secondary particle size distribution can be obtained in the subsequent pulverization process, and the larger initial particle size helps to form a good crystal structure during high temperature treatment.

[0037] It can be understood that the particle size distribution parameter of the lithium iron phosphate material is an important factor affecting the performance of the lithium iron phosphate material.

[0038] By precisely controlling the molar ratios of lithium source to iron source, and iron source to phosphorus source, the stoichiometric ratio of the material is optimized, which helps to reduce structural defects, thereby increasing the capacity of the lithium iron phosphate material and making it closer to the theoretical capacity; by combining a high-temperature treatment process, a lithium iron phosphate substrate with a good crystal structure is formed, the compaction density of the powder is increased, and a material that meets the particle size requirements is obtained through pulverization, further optimizing the specific surface area and particle distribution of the material, enhancing the conductivity and ion mobility of the material, thereby improving the fast charging performance of lithium-ion batteries, and improving the overall first charge and discharge efficiency and cycle life of lithium-ion batteries; in addition, despite the improved performance, the lithium iron phosphate material still maintains its high safety and cost-effectiveness, meeting the fast charging needs without reducing the power, making it continue to be competitive in the field of power batteries and able to effectively respond to technical challenges under fast charging conditions.

[0039] In a specific embodiment, the mass ratio of iron to phosphorus in the lithium iron phosphate material is 1.74-1.80, the mass ratio of carbon content is 0.9-1.2%, and the degree of graphitization is 0.7-0.95.

[0040] Exemplarily, the iron-phosphorus mass ratio in the lithium iron phosphate material can be 1.74, 1.745, 1.75, 1.755, 1.76, 1.765, 1.77, 1.775, 1.78, 1785, 1.79, 1.795, 1.80 or a range consisting of any two of them. By controlling the iron-phosphorus mass ratio between 1.74 and 1.80, the stoichiometric ratio of the material can be ensured to be close to the ideal value. This optimization helps to reduce non-stoichiometric defects in the material, thereby increasing the capacity of the lithium iron phosphate material, making it closer to the theoretical capacity, and thus improving the energy density of the lithium-ion battery; the carbon content mass ratio can be 0.9%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.0%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1.2% or a range consisting of any two of them, which helps to form a uniform carbon coating on the surface of the lithium iron phosphate particles, significantly improves the conductivity of the lithium iron phosphate material, promotes the transmission of electrons in the electrode, thereby improving the rate performance and fast charging capability of the lithium ion battery, and the carbon coating can also enhance the structural stability of the material and extend the cycle life of the lithium ion battery; the degree of graphitization can be 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or a range consisting of any two of them, indicating that the carbon layer has a good degree of graphitization, which helps to improve the conductivity of the lithium iron phosphate material, thereby further enhancing the electrochemical performance of the lithium ion battery.

[0041] In a specific embodiment, the lithium iron phosphate material satisfies at least one of the following: the D50 particle size of the lithium iron phosphate material is 0.9-1.5 μm; (D90-D10) / D50 of the lithium iron phosphate material is greater than or equal to 3.1; and the average primary particle size of the lithium iron phosphate material is 200-400 μm.

[0042] Exemplarily, the D50 particle size of the lithium iron phosphate material is 0.9μm, 0.95μm, 1.0μm, 1.05μm, 1.1μm, 1.15μm, 1.2μm, 1.25μm, 1.3μm, 1.35μm, 1.4μm, 1.45μm, 1.5μm or a range consisting of any two of them. By controlling the D50 particle size within the range of 0.9-1.5μm, it helps to optimize the specific surface area and inter-particle contact of the material, improve the conductivity and ion mobility of the material, thereby enhancing the fast charging performance and overall electrochemical efficiency of the battery.

[0043] Exemplarily, (D90-D10) / D50 of the lithium iron phosphate material is a value greater than or equal to 3.1, for example, 3.1, 3.11, 3.12, 3.13, 3.14, 3.15, 3.16, 3.17, 3.18, 3.19, 3.2 or a range consisting of any two of them; (D90-D10) / D50 greater than or equal to 3.1 means that the particle size distribution is wide, allowing a certain degree of particle size variation, which helps to increase the compaction density of the material because particles of different sizes can better fill the electrode space and reduce porosity, and the wide particle size distribution can enhance the mechanical stability of the electrode and reduce structural changes during charge and discharge cycles.

[0044] Exemplarily, the average primary particle size of the lithium iron phosphate material can be 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm, 300μm, 310μm, 320μm, 330μm, 340μm, 350μm, 360μm, 370μm, 380μm, 390μm, 400μm or a range consisting of any two of them. The larger average primary particle size provides sufficient mechanical strength and stability, so that a uniform secondary particle size distribution can be obtained in the subsequent crushing process, and the larger initial particle size also helps to form a good crystal structure during high temperature treatment, ensuring the stability and durability of the material in the electrochemical reaction.

[0045] In a specific embodiment, in step (1), the amount of carbon source added is determined according to 0.9-1.2% of the mass of the lithium iron phosphate material.

[0046] Exemplarily, the amount of carbon source added can be determined according to 0.9%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.0%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.2% of the mass of the lithium iron phosphate material, or a range composed of any two of them. By precisely controlling the amount of carbon source added within the range of 0.9-1.2% of the mass of the lithium iron phosphate material, it can be ensured that the material has good conductivity and electrochemical properties, and the formation of the carbon coating layer also helps to improve the conductivity and cycle stability of the material, so that it exhibits excellent performance in lithium-ion battery applications.

[0047] In a specific embodiment, in step (2), the temperature of the high temperature treatment is 750-850°C.

[0048] Exemplarily, the temperature of the high temperature treatment is 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C or a range consisting of any two of them. By controlling the temperature of the high temperature treatment to 750-850°C, the components in the precursor can be promoted to fully react to form a lithium iron phosphate substrate with good crystallinity. Good crystallinity helps to improve the electrochemical properties of the material.

[0049] In a specific embodiment, in step (2), the heating rate of the high temperature treatment is 5°C / min, and after reaching 750°C, the temperature is maintained for 8-16 hours.

[0050] Exemplarily, the heating rate of high temperature treatment is 5°C / min, and the holding time after reaching 750°C can be selected as 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h or a range consisting of any two of them. The slower heating rate helps to heat the material uniformly, reduce the stress and defects caused by the temperature gradient, thereby promoting uniform crystal growth, reducing defects in the crystal structure, and improving the crystallinity of the material. A sufficiently long holding time allows the crystal structure to fully mature and stabilize, further improving the crystallinity and phase purity of the material, which is crucial to improving the electrochemical properties of the material (such as specific capacity and cycle stability). By selecting a heating rate of 5°C / min and a 750°C holding time of 8-16 hours, the structure and performance of the lithium iron phosphate material can be significantly optimized, so that it exhibits excellent electrochemical performance and stability in lithium-ion battery applications.

[0051] In a specific embodiment, the iron source is selected from one or more of FeSO4, FePO4, FeCl3, FeC2O4, Fe2O3; and / or the lithium source is selected from one or more of Li2CO3, LiH2PO4, Li3PO4; and / or the phosphorus source is selected from one or more of NH4H2PO4, H3PO4.

[0052] In a specific embodiment, the reagent serving as a reducing agent and a carbon source is selected from one or more of C2H2, CH4, glucose, polyethylene glycol, sucrose, starch, H2, and CO.

[0053] The present application also provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer is selected from the lithium iron phosphate material obtained by the preparation method described above.

[0054] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.

[0055] The present application also provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the positive electrode sheet described above.

[0056] The present application does not strictly limit the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.

[0057] The present application does not strictly limit the selection of electrolyte, and may include one or more of the solvents commonly used in lithium-ion battery electrolytes, and electrolyte lithium salts commonly used in lithium-ion electrolytes, for example: the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, cyclopentane, γ-butyrolactone, etc.; the lithium salt may be, for example, one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0058] The present application does not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in lithium-ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven diaphragm, or a diaphragm with a ceramic coating.

[0059] The present application does not specifically limit the method for preparing the battery, and the battery can be prepared by referring to conventional methods in the art.

[0060] For example, in a specific embodiment, a lithium ion battery can be prepared by the following steps:

[0061] The positive electrode sheet, separator and negative electrode sheet are placed in sequence, and then the battery cell assembly is obtained by winding or stacking, and then the lithium-ion battery is obtained after processes such as liquid injection, formation, and capacity division.

[0062] The present application also provides an electrical device, comprising the lithium-ion battery described above.

[0063] The present application does not specifically limit the electrical equipment, which may be any electrical equipment including the lithium-ion battery, including but not limited to mobile phones, portable devices, laptop computers, electric bicycles, electric cars, electric toys, and energy storage devices.

[0064] Hereinafter, the lithium iron phosphate material and lithium ion battery provided by the present application will be further introduced in conjunction with specific embodiments.

[0065] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0066] Example 1

[0067] This embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is as follows:

[0068] 1. Preparation of lithium iron phosphate materials

[0069] The molar ratio of the raw material iron source to the phosphorus source is controlled to be 0.98, the molar ratio of the lithium source to the iron source is controlled to be 1.03, and a carbon source accounting for 1.1% of the mass of the lithium iron phosphate material is added, the carbon source is composed of polyethylene glycol and glucose in a mass ratio of 6:4, and pure water is used as a medium. The mixture is ground and mixed in a sand mill to ensure that the test slurry particle size D50 is less than 0.4μm. A spray drying device is used to perform solid-liquid separation on the test slurry to obtain a precursor powder; the precursor powder is placed in a nitrogen atmosphere, heated to 750℃ at a heating rate of 5℃ / min, and kept warm for 9h to obtain a lithium iron phosphate substrate; the lithium iron phosphate substrate is pulverized by airflow, and the D50 particle size and (D90-D10) / D50 are controlled to obtain a lithium iron phosphate material.

[0070] 2. Preparation of positive electrode

[0071] For example, the lithium iron phosphate material prepared as above is used as the positive electrode active material, dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent with a conductive agent and a binder, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and after drying, rolling and slitting, a positive electrode sheet is obtained. The compacted density of the positive electrode sheet is not less than 2.7g / cm3.

[0072] 3. Preparation of lithium-ion batteries

[0073] The positive electrode sheet prepared as above and the selected negative electrode sheet are placed in a high-temperature oven at 110°C and baked for 7 hours to remove moisture from the electrode sheets; the positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and after further winding into a square bare battery cell, an aluminum-plastic film is inserted, and the corresponding electrolyte is injected and sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a lithium-ion battery with a nominal capacity of 2Ah is obtained.

[0074] Among them, the negative electrode sheet uses a conventional lithium-ion battery negative electrode sheet, such as the Shanshan QCG-X9 model negative electrode, whose electrode sheet compaction density is not less than 1.6g / cm3, and the negative electrode active material is amorphous carbon-coated graphite; the composition of the electrolyte is EC:DEC:EMC=4:3:3, the mass proportion of additives is 10% of the total mass, the composition of the additives is VC:PS:FEC:CHB=3:2:1:1, and the concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L.

[0075] Example 2

[0076] This embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, the molar ratio of the iron source to the phosphorus source is adjusted to 0.985.

[0077] Example 3

[0078] This embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, the molar ratio of the iron source to the phosphorus source is adjusted to 0.975.

[0079] Example 4

[0080] The present embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, an adjustment is made to add a carbon source accounting for 1.2% of the mass of the lithium iron phosphate material, and the carbon source is composed of polyethylene glycol and glucose in a mass ratio of 6:4.

[0081] Example 5

[0082] The present embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, an adjustment is made to add a carbon source accounting for 0.95% of the mass of the lithium iron phosphate material, and the carbon source is composed of polyethylene glycol and glucose in a mass ratio of 6:4.

[0083] Example 6

[0084] The present embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, an adjustment is made to add a carbon source accounting for 1.1% of the mass of the lithium iron phosphate material, and the carbon source is composed of polyethylene glycol and glucose in a mass ratio of 7:3.

[0085] Example 7

[0086] The present embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, an adjustment is made to add a carbon source accounting for 1.1% of the mass of the lithium iron phosphate material, and the carbon source is composed of polyethylene glycol and glucose in a mass ratio of 5:5.

[0087] Example 8

[0088] This embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is substantially the same as that of Embodiment 1, except that, in the preparation of the lithium iron phosphate material, D50 is controlled to be 1.4 μm.

[0089] Example 9

[0090] This embodiment provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Embodiment 1, except that, in the preparation of the lithium iron phosphate material, D50 is controlled to be 1.0 μm.

[0091] Comparative Example 1

[0092] This comparative example provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, the molar ratio of the iron source to the phosphorus source is adjusted to 0.99.

[0093] Comparative Example 2

[0094] This comparative example provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, the molar ratio of the iron source to the phosphorus source is adjusted to 0.96.

[0095] Comparative Example 3

[0096] This comparative example provides a lithium iron phosphate material, a positive electrode sheet and a lithium ion battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the lithium iron phosphate material, the material is heated to 780° C. at a heating rate of 5° C. / min.

[0097] Test Case

[0098] 1. Average primary particle size test

[0099] Test method: The lithium iron phosphate materials obtained in the above embodiment and comparative example were observed for particle morphology using a scanning electron microscope (SEM), and 100 particles were randomly selected for measurement, and the average value of the primary particle size was calculated as the average primary particle size of the lithium iron phosphate material, thereby obtaining the average primary particle size of the lithium iron phosphate material corresponding to the above embodiment and comparative example, and the value is listed in Table 1. For example, Figure 1 This is a SEM image of the lithium iron phosphate material provided in this application. Figure 1 As shown, the red circle in the figure is the primary particle size of the lithium iron phosphate material particles.

[0100] 2. Secondary particle size test

[0101] Test method: Take samples of the lithium iron phosphate materials in the above-mentioned embodiments and comparative examples respectively, ensure that the samples are uniform and free of agglomeration, disperse the samples in an appropriate medium (usually a liquid, such as water or ethanol) to ensure that the particles are fully dispersed, and inject the dispersed samples into a laser particle size analyzer. The laser particle size analyzer measures the angle and intensity of laser scattering to calculate the particle size distribution of the lithium iron phosphate material particles corresponding to the above-mentioned embodiments and comparative examples, which are usually expressed in terms of parameters such as D10, D50, and D90, and the corresponding values ​​of D50 and (D90-D10) / D50 are listed in Table 1.

[0102] 3. Powder compaction density test

[0103] Test method: Weigh 1 g of the lithium iron phosphate material in the above-mentioned embodiment and comparative example respectively, and add it into a cylindrical mold, the cross-sectional area of ​​the circular hole of the mold is S; apply a pressure of 3t to the powder in the mold, and maintain the pressure for 30s, record the powder thickness as t, and calculate the powder compaction density ρ of the lithium iron phosphate material corresponding to the above-mentioned embodiment and comparative example respectively by the formula ρ=m / (S×t), and the value is listed in Table 2.

[0104] 4. Graphitization degree test

[0105] Test method: Weigh 1g of lithium iron phosphate materials in the above embodiment and comparative example respectively, and use a 532nm laser to irradiate the sample. When the laser interacts with the sample, it will cause the carbon atoms in the sample to vibrate and produce Raman scattering; use a DXR3xi ultra-fast imaging Raman spectrometer and a 50x telephoto objective to collect scattered light and generate a spectrum. For carbon materials, the most important characteristic peaks in the Raman spectrum are the D peak (about 1350 cm⁻¹) and the G peak (about 1580 cm⁻¹). cm⁻¹), where the G peak corresponds to the ordered structure of graphitized carbon, while the D peak is related to defects or amorphous carbon; with the increase of laser power, the amorphous carbon layer coated on the surface of the sample may be burned to expose the internal lithium iron phosphate, because amorphous carbon is more sensitive to laser, while graphitized carbon is relatively more stable; through the deconvolution technique, the D peak and G peak in the Raman spectrum are separated, and the intensity ratio of the D peak to the G peak (ID / IG) is calculated, and the value is listed in Table 1. This ratio is a key indicator for evaluating the degree of graphitization. A lower ID / IG ratio usually indicates a higher degree of graphitization, which means that there are more ordered graphitized carbon structures in the sample.

[0106] 5. Carbon content test

[0107] Test method: Take the lithium iron phosphate material samples in the above embodiments and comparative examples, place the samples in a thermogravimetric analyzer (TGA), and gradually increase the temperature under an inert atmosphere (such as nitrogen); determine the carbon content by measuring the change in the mass of the sample with temperature, thereby obtaining the carbon content of the lithium iron phosphate material corresponding to the above embodiments and comparative examples, and list the values ​​in Table 1. Among them, the carbon content is usually expressed as a mass percentage, reflecting the degree of carbon coating in the material.

[0108] 6. 0.1C charging capacity in grams and 1C discharging capacity in grams test

[0109] Test method: The lithium-ion batteries in the above embodiments and comparative examples are subjected to charge and discharge tests. A specific charge and discharge cycle process is as follows: Use 0.1C current for constant current charging until the voltage reaches 3.65V, switch to constant voltage charging mode, and continue charging until the charging current is less than 0.05C and then cut off. After charging is completed, pause for 5 minutes; Use 0.1C current for constant current discharge until the voltage drops to 2.5V. After discharging, pause for 5 minutes again; The above constitutes a normal temperature charge and discharge cycle of the lithium-ion battery. Correspondingly, add the 0.1C constant current charging capacity to the constant voltage charging capacity, and divide it by the mass of the lithium iron phosphate positive electrode active material to obtain the 0.1C charging gram capacity, and list the value in Table 2; Fully charge the lithium-ion battery at room temperature, discharge it to 2.5V with a 1C current constant current, divide the 1C discharge capacity by the mass of the lithium iron phosphate material, and obtain the 1C discharge gram capacity, and list the value in Table 2.

[0110] 7. 45℃ Cyclic Performance Test

[0111] Test method: The lithium-ion batteries in the above embodiments and comparative examples were placed in a 45°C oven for 2 hours, and then subjected to charge and discharge tests. A specific charge and discharge cycle process is as follows: Use a 1C current for constant current charging until the voltage reaches 3.65V, switch to constant voltage charging mode, and continue charging until the charging current is less than 0.05C, then cut off. After charging is completed, pause for 5 minutes; use a 1C current for constant current discharge until the voltage drops to 2.5V. After discharging, pause again for 5 minutes. The above is a charge and discharge cycle of the lithium-ion battery. Repeat the cycle process until 500 cycles are reached. Then calculate the ratio of the lithium-ion battery capacity to the initial capacity, and list the value in Table 2. This value can be used to evaluate the cycle performance of the lithium-ion battery at 45°C.

[0112] Table 1

[0113]

[0114] Table 2

[0115]

[0116] The following conclusions can be drawn from Table 1 and Table 2:

[0117] 1) By comparing and analyzing the test results of the embodiments and the comparative examples, it can be seen that in Example 2, as the iron-phosphorus ratio is further improved, the reaction activity of the material decreases, the average primary particle size becomes smaller, the powder compaction density decreases slightly, the 0.1C charge gram capacity increases, and the rate performance 1C discharge gram capacity improves, but the high temperature cycle performance shows a slight downward trend.

[0118] 2) Example 3: As the iron-phosphorus ratio decreases, the average primary particle size increases slightly, the powder compaction density increases, the 0.1C charge gram capacity decreases, the rate performance 1C discharge gram capacity is slightly worse, and the high temperature cycle performance is slightly better.

[0119] 3) Example 4 As the carbon content increases, the proportion of positive electrode active material decreases, the powder compaction density and 0.1C charge gram capacity slightly decrease, but the rate performance 1C discharge gram capacity slightly improves, and the high temperature cycle performance slightly improves.

[0120] 4) Example 5 As the carbon content decreases, the proportion of positive electrode active material increases, the powder compaction density and 0.1C charge gram capacity increase, but the rate performance 1C discharge gram capacity is slightly worse.

[0121] 5) Example 6 As the proportion of polymer carbon source increases, the carbon coating density and graphitization degree increase, ID / IG decreases, the powder compaction density increases, the 0.1C charge gram capacity remains unchanged, but the rate performance 1C discharge gram capacity and cycle performance are improved.

[0122] 6) Example 7: As the proportion of polymer carbon source decreases, the carbon coating density and graphitization degree decrease, ID / IG increases, the powder compaction density is slightly lower, the 0.1C charge gram capacity remains unchanged, and the rate performance 1C discharge gram capacity and cycle performance are slightly reduced.

[0123] 7) Example 8 As the D50 particle size increases, the powder compaction density increases, and the lithium desorption distance increases, resulting in a slightly lower 0.1C charge gram capacity and rate performance 1C discharge gram capacity, and the cycle performance is improved.

[0124] 8) Example 9 As the D50 particle size decreases, the powder compaction density decreases, and the shortening of the lithium desorption distance leads to improvements in the 0.1C charge gram capacity and rate performance 1C discharge gram capacity, but the cycle performance is slightly worse.

[0125] 9) When the iron-phosphorus ratio of comparative example 1 is too high, the growth and development of the positive electrode material is poor, the average primary particle size is small and the powder compaction density is low; in addition, the increase in impurity iron leads to a decrease in the 0.1C charge gram capacity, the rate performance 1C discharge gram capacity deteriorates, and the high-temperature cycle deteriorates sharply due to the increase in iron dissolution.

[0126] 10) When the iron-phosphorus ratio of comparative example 2 is too low, the active iron sites of the positive electrode material are reduced and the average primary particle size becomes larger. Although the powder compaction density is high and the cycle performance is excellent, the 0.1C charging gram capacity is the same as that of the current conventional lithium iron phosphate material, and the purpose of increasing capacity cannot be achieved.

[0127] 11) In comparative example 3, as the degree of graphitization increases, ID / IG decreases. In order to further increase the degree of graphitization, in addition to increasing the proportion of polymer carbon source, it is necessary to increase the sintering temperature, which leads to an increase in the average primary particle size. Although the powder compaction density increases, the 0.1C charge gram capacity and rate performance 1C discharge gram capacity deteriorate sharply, and do not meet the performance requirements.

[0128] In summary, when preparing lithium iron phosphate materials, by precisely controlling key indicators such as the iron-phosphorus ratio, carbon content, degree of graphitization, and particle size, and combining with optimized processing technology, high-capacity and high-compacted lithium iron phosphate materials can be obtained, and the iron-phosphorus mass ratio of the lithium iron phosphate material is 1.74-1.80, the carbon content mass ratio is 0.9-1.2%, and the degree of graphitization is 0.7-0.95; the lithium-ion battery prepared based on this lithium iron phosphate material exhibits excellent performance, with a 0.1C charging gram capacity ≥162mAh / g, a powder compaction density ≥2.6g / cm3, and a rate performance of 1C discharge gram capacity>138mAh / g, and while improving the capacity and powder compaction density, it also has good cycle performance.

[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a lithium iron phosphate material, characterized in that: include: (1) mixing raw materials of an iron source, a lithium source, and a phosphorus source, and reagents serving as a reducing agent and a carbon source, and grinding the mixture to obtain a precursor powder; wherein the molar ratio of the lithium source to the iron source is 1.03-1.05, and the molar ratio of the iron source to the phosphorus source is 0.965-0.99; (2) treating the precursor powder at high temperature under an inert atmosphere to obtain a lithium iron phosphate substrate; (3) The lithium iron phosphate substrate is crushed to obtain a lithium iron phosphate material that meets the particle size requirements.

2. The preparation method according to claim 1, characterized in that: The mass ratio of iron to phosphorus in the lithium iron phosphate material is 1.74-1.80, the mass ratio of carbon content is 0.9-1.2%, and the degree of graphitization is 0.7-0.

95.

3. The preparation method according to claim 1 or 2, characterized in that: The lithium iron phosphate material meets at least one of the following requirements: The D50 particle size of the lithium iron phosphate material is 0.9-1.5 μm; The (D90-D10) / D50 of the lithium iron phosphate material is greater than or equal to 3.1; The average primary particle size of the lithium iron phosphate material is 200-400 μm.

4. The preparation method according to claim 1 or 2, characterized in that: In step (1), the amount of the carbon source added is determined according to 0.9-1.2% of the mass of the lithium iron phosphate material.

5. The preparation method according to claim 1 or 2, characterized in that: In step (2), the temperature of the high temperature treatment is 750-850°C.

6. The preparation method according to claim 5, characterized in that: In step (2), the heating rate of the high temperature treatment is 5°C / min, and after reaching 750°C, the temperature is kept at this temperature for 8-16 hours.

7. The preparation method according to claim 1 or 2, characterized in that: The iron source is selected from one or more of FeSO4, FePO4, FeCl3, FeC2O4, and Fe2O3; And / or, the lithium source is selected from one or more of Li2CO3, LiH2PO4, Li3PO4; And / or, the phosphorus source is selected from one or more of NH4H2PO4 and H3PO4.

8. The preparation method according to claim 1 or 2, characterized in that: The reagent used as a reducing agent and carbon source is selected from one or more of C2H2, CH4, glucose, polyethylene glycol, sucrose, starch, H2, and CO.

9. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode active material layer is selected from the lithium iron phosphate material obtained by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet includes the positive electrode sheet as claimed in claim 9.

11. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 10.

Citation Information

Cited By

  • Lithium ion secondary battery, battery device, and power device

    CN120073043A

  • Lithium-ion secondary batteries, battery devices and electrical appliances

    CN120073043B

  • Evaluation method and application of electrochemical performance of lithium iron phosphate positive electrode material

    CN120539247A

  • Lithium-ion secondary battery, battery apparatus, electric apparatus, preparation method for positive electrode active material, and preparation method for positive electrode plate

    US12770878B2

  • Preparation method for lithium iron phosphate material, lithium-ion battery, and electric device

    WO2026118408A1